Forehead flap: a reconstructive option in selected complex defects following resection of oral cancers staged T4 - Kenkere, Deepika; Mohiyuddin, S. M. Azeem; Deo, Ravindra P.; A., Sagayaraj; Mohammadi, Kouser; Babu, Prashanth; Merchant, Shuaib; K. R., Sumanth; K. S., Gopinath (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Head and neck squamous carcinoma constitutes 30% of malignancies in our region, oral carcinoma being most common among them. Most of these tumours involve lower gingivobuccal sulcus and buccal mucosa. 80% patients present with locally advanced disease. Following resection of these tumours, reconstruction of composite defects is challenging. Though microvascular free flaps are ideal in such cases, it is not always feasible due to malnutrition, peripheral vascular disease, sometimes non–availability of microvascular surgeon and financial constraints. Pectoralis major myocutaneous flap, the workhorse of reconstruction is bulky, non-pliable and cannot be advanced over intact mandible. Forehead flap in complex defects is pliable, versatile, has excellent vascularity and colour matching, easy to harvest and suitable in selected cases and as salvage flap when other flaps fail. The aim of the study was to document outcome of folded forehead flap reconstruction of complex defects following resection of T4 staged oral carcinoma. Methods: This retrospective study in a tertiary rural hospital included 31 patients with oral carcinoma staged T4. The patients underwent folded forehead flap reconstruction for full thickness cheek defects with some extending into oral commissure and lower lip, along with segmental or alveolar resection of mandible or maxilla. Results: 27 patients had uneventful healing, 2 had wound dehiscence and 2 had necrosis of distal part of flap. Patients with externally rotated flap had mild trismus and patients in whom forehead flap was used to reconstruct the oral commissure had oral incompetence. Conclusions: Folded forehead flap is good reconstructive option in complex full thickness defects of cheek and as salvage reconstruction.